2008
DOI: 10.1192/bjp.bp.107.038208
|View full text |Cite
|
Sign up to set email alerts
|

Immigrants and borderline personality disorder at a psychiatric emergency service

Abstract: Our results showed that in the psychiatric emergency service borderline personality disorder was diagnosed less frequently in the immigrant group v. the indigenous group. Our results do not support the concept of migration as a risk factor for borderline personality disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 23 publications
3
23
2
3
Order By: Relevance
“…Castaneda and Franco (1985) found no ethnic group differences in rates of BPD, whereas the study of Pascual et al (2008) showed that immigrants in a psychiatric emergency service had a lower likelihood of being diagnosed with BPD.The aim of the present study was to compare the frequency of borderline personality disorder in psychiatric inpatients with an immigrant background vs. the indigenous group.A total of 2494 consecutive patients over a three-year period at a psychiatric university hospital were reviewed. The few studies regarding the prevalence of borderline personality disorder (BPD) in immigrants compared to an indigenous population are inconsistent.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Castaneda and Franco (1985) found no ethnic group differences in rates of BPD, whereas the study of Pascual et al (2008) showed that immigrants in a psychiatric emergency service had a lower likelihood of being diagnosed with BPD.The aim of the present study was to compare the frequency of borderline personality disorder in psychiatric inpatients with an immigrant background vs. the indigenous group.A total of 2494 consecutive patients over a three-year period at a psychiatric university hospital were reviewed. The few studies regarding the prevalence of borderline personality disorder (BPD) in immigrants compared to an indigenous population are inconsistent.…”
supporting
confidence: 85%
“…

Information about the relationship between personality disorder and ethnicity or migration is sparse. The difference between the indigenous and the immigrant group regarding the rates of BPD-diagnoses was statistically significant (chi 2 =5,02, df=1, p=0,025).In accordance to the findings of Pascual et al (2008) and challenging the results of Castaneda and Franco (1985), our findings suggest that in a clinical sample BPD was diagnosed less frequently in the immigrant group than in the indigenous group. Castaneda and Franco (1985) found no ethnic group differences in rates of BPD, whereas the study of Pascual et al (2008) showed that immigrants in a psychiatric emergency service had a lower likelihood of being diagnosed with BPD.

The aim of the present study was to compare the frequency of borderline personality disorder in psychiatric inpatients with an immigrant background vs. the indigenous group.

A total of 2494 consecutive patients over a three-year period at a psychiatric university hospital were reviewed.

…”
mentioning
confidence: 98%
“…Pascual et al (2008) found that all patients were similar, independent of region of origin, with no significant difference between subgroups in gender, risk of suicide, risk of danger to others, or family disruption. However, patients with BPD from North Africa and sub-Saharan Africa were younger, and those from Asia were older than the indigenous group.…”
Section: Immigrants In Spainmentioning
confidence: 88%
“…Hispanic immigrants more often diagnosed with BPD than White or Black patients in the U.S. Castaneda and Franco (1985); Chavira et al (2003) Immigrants with lower rates of BPD diagnoses than indigenous populations Baleydier et al (2003) in Switzerland; Pascual et al (2008) in Spain; Nielsen et al (2011) in Germany self-harming behaviors, and more thoughts of interpersonal aggression than White patients. Differences in affective symptoms were accounted for by group differences in substance use and receipt of inpatient services, whereas differences in behavioral symptomatology persisted after adjusting for potential confounders, demonstrating that the BPD experience may differ substantially across races.…”
Section: Race and Identification Of Borderline Personality Disordermentioning
confidence: 97%
See 1 more Smart Citation